Computational and Experimental Study of the Dynamic Loading of the Tracked and Wheeled Vehicles Powertrain System in Harsh Climatic Conditions - Taratorkin, Alexander Igorevich; Taratorkin, Igor Alexandrovich; Derzhanskii, Victor Borisovich; Volkov, Alexander Alexandrovich (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2025)
The article presents the results of a computational and experimental study of the dynamic loading of the powertrain system of the transport vehicles, which include a diesel engine and a hydromechanical transmission. The purpose of the study is a computational and experimental substantiation of the applicability of torsion bar spring between the engine and transmission as a torsional oscillation damper in the powertrain system with diesel engines of increased power and high-density arrangement of the block elements, which makes it difficult to apply traditional measurement methods. The novelty of the research consists in the development of a new method to determine experimentally the dynamic torque in the powertrain system, characterized by the fact that during processing, the signal of the engine shaft speed sensor is digitized and transmitted to the recording and processing device. Based on the direct Fourier transform, the amplitude-frequency response function of the torque is determined, including the main motor harmonics, harmonic components formed by the crankshaft and connecting rod and gas valve timing mechanisms of the engine, the generator drive, oscillations in the transmission, etc. It is established that the reason for the torsion bar springs durability limitation is their operation in off-design powertrain system modes, due to the occurrence of a phenomenon called «collision of tasks». Based on probabilistic calculation methods, it is shown that when such modes occur, the probability of failure of elastic torsion bar increases from 0.0001 to a shocking 0.29. According to the research results, it is concluded that torsion bar springs are applicable as torsional vibration dampers in high-duty powertrain systems.